ANALISIS PENJADWALAN PRODUKSI UNTUK MEMINIMALKAN STOCK OUT GUNA MEMENUHI TARGET PERMINTAAN - Zamroni, Moh Shiddiq; Arief, Zainal (LPPM Universitas Bina Bangsa, 2023)
Production management is responsible for making smart decisions regarding the most suitable production strategy for the future, focusing on reducing costs as efficiently as possible while increasing profit potential. UD Inti Jaya is a business engaged in building, namely the manufacture of tile from clay. UD. Inti Jaya has used various different methods of production planning and raw material inventory management. In order to improve the efficiency and effectiveness of production planning, the company has implemented several methods and techniques. First, the company uses the method of forecasting product demand for future periods. The results of this forecasting are used for production planning using aggregate planning methods, especially the Trial-and-Error method. To determine raw material needs, here the company uses the Economic Order Quantity (EOQ) method to calculate raw material inventory needs with the aim of minimizing inventory costs. Results from the use of the EOQ method shows that the inventory cost of raw materials produced is smaller compared to the previous inventory policy used by the company. This indicates that the EOQ method provides better efficiency in raw material inventory management, reduces inventory costs and allows companies to have appropriate safety stock and reorder more effectively. Thus, the conclusion that can be drawn is that the application of the EOQ method in raw material inventory management provides better results, with lower inventory costs compared to previous policies implemented by the company. This illustrates that using the EOQ method can help companies in more efficient and effective inventory management.